Modeling traffic accidents : a case study of Sun Yat-Sen National Freeway, Taiwan - Wang, Shih-chueh; Chen, Jian-Shiuh; Yordphol Tanaboriboon; Morisugi, Hisa; Government of Republic of China (Bangkok : Asian Institute of Technology, 1997)
The cost of Taiwanese accidents is estimated to exceed U.S.$ 100 million annually. During the period of 1975-1995, 5,365 vehicle accidents, 3,177 fatalities and 9,478 injuries were reported on the Sun Yat-Sen National Freeway that is the major expressway from northern to southern Taiwan. In addition to losses on injuries, fatalities, and property damage, traffic delays, congestion, and associated social-cost loss have cause major concerns about highway safety. A systematic highway safety improvement strategy then becomes urgent for highway agencies. The main purpose of this study is to identify hazardous locations and to develop predictive models that can help highway agencies to propose the safety improvement strategies, to aid the planning, design, and the operation of the freeway, so as to ensure the safety of lives and properties. The hazardous locations were first identified by using the accident frequency method, the accident rate method, matrix method, the rate quality control method, the equivalent traffic accident number (ET AN) method, and critical accident rate method. The results revealed that road sections such as toll stations, interchanges, emergency landing strips (the road sections without medians), and large downgrade road sections are more hazardous than the others. The merits and flaws of these methods were also compared in the study. In modeling the traffic accidents and a given set of the geometric design and traffic, two conventional linear regression models and two Poisson regression models were investigated and compared in the study. Explanatory variables involved in models included the divided or undivided medians, number of lanes, vertical grade, horizontal curvature, and average speed of the vehicles. Poisson regression models were shown to be more suitable to describe the random, discrete, non-negative, and sporadic vehicle accident events than the conventional regression models. The results indicated that traffic accidents of undivided road that is designed for the emergency landing strips is significantly higher than those divided roads. The accident frequency of two-lane road is more significant and higher than the others. Higher traffic accidents happened on the descent road than the ascent road, and the accident frequency of road with small radius is higher than the larger one. The speed is also shown to have the positive effect on the accident frequency.
Thesis (M.Eng.) - Asian Institute of Technology, 1996
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Keywords: Traffic accidents -- Taiwan